Accidental Formation of Eutectics during Crystal Engineering of Lamotrigine with Solubility Advantage and Drug Release Efficiency - Kulkarni, Deepak (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: Lamotrigine (LMG) is the Biopharmaceutical Classification System Class-II drug with hurdle in drug release and dissolution efficiency due to poor water solubility. The present investigation was aimed to improve the solubility and dissolution of LMG by crystal engineering by formation of cocrystals but which accidently turn toward eutectics formation. Methods: LMG was subjected to neat grinding with different Cocrystal Formers (CCF) to develop multicomponent crystalline system. The prepared multicomponent system was analyzed by Differential Scanning Calorimetry, Raman spectroscopy, and Powder X-ray Diffraction reveals the formation of multicomponent system. Improved dissolution was interpreted by comparative drug release study of tablet formulation of unprocessed drug and eutectics. Results: There was unplanned formation of eutectics of LMGAscorbic acid (LMG-AA) that was observed with improved drug solubility. LMG-AA eutectics showed enhanced solubility (651.61 ± 1.02 μg/ml) in comparison with pure drug (161.46 ± 0.86 μg/ml) and all remaining multicomponent systems formed with other CCF’s. The LMG-AA eutectics showed comparatively better drug release than pure LMG tablet. LMG eutectics also showed significant improvement in flow properties and compressibility as compared to pure drug. Conclusion: Multicomponent LMG-AA eutectics although formed in unplanned way they effectively enhances the solubility of LMG serving the main purpose of the research work. It can be utilized efficiently for drug delivery due to its improved dissolution and better drug release.